2015
DOI: 10.3390/genes6030734
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Topological Domains and Loop Formation to 3D Chromatin Organization

Abstract: Recent investigations on 3D chromatin folding revealed that the eukaryote genomes are both highly compartmentalized and extremely dynamic. This review presents the most recent advances in topological domains’ organization of the eukaryote genomes and discusses the relationship to chromatin loop formation. CTCF protein appears as a central factor of these two organization levels having either a strong insulating role at TAD borders, or a weaker architectural role in chromatin loop formation. TAD borders directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 59 publications
4
45
1
Order By: Relevance
“…3). Numerous studies performed in human and murine cultured and primary cell lines have identified CTCF as a key regulator of TAD formation in mammals [4, 5254]. However, we do not see the loss of TADs or dramatic changes in the TAD profile in differentiated HD3 cells in spite of dramatic loss of CTCF occupancy at the binding sites within the studied area (Fig.…”
Section: Discussioncontrasting
confidence: 59%
“…3). Numerous studies performed in human and murine cultured and primary cell lines have identified CTCF as a key regulator of TAD formation in mammals [4, 5254]. However, we do not see the loss of TADs or dramatic changes in the TAD profile in differentiated HD3 cells in spite of dramatic loss of CTCF occupancy at the binding sites within the studied area (Fig.…”
Section: Discussioncontrasting
confidence: 59%
“…Specifically, CTCF has many roles in regulating gene expression as an insulator and in its role in chromatin architecture 2426 . Data published in ENCODE 27 using multiple cell lines including small airway epithelial cells (SAEC) indicated that CTCF binds to this region 28 , so we tested CTCF binding affinity to the IFITM3 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…TAD boundaries were found to be enriched in binding sites to proteins CTCF (CCCTC-binding factor) and cohesin, as well as to transcription start sites, histone marks of active chromatin, housekeeping genes, and short interspersed nuclear elements. 45 CTCF is a highly conserved transcription factor that can act as a transcriptional activator, repressor, and insulator; it is involved in many cellular processes, including regulation of chromatin structure. 46 Cohesin is a multisubunit protein, ring-shaped complex composed of four core subunits: two SMC proteins (SMC1 and 3), an alpha-kleisin (Rad21/Scc1), and an orthologue of the yeast Scc3 protein.…”
Section: Tad Related Proteinsmentioning
confidence: 99%